Medium-sized and large mammals from Quedas do Rio Bonito Ecological Park, Minas Gerais, Brazil - Santos, Kassius Klay; Pacheco, Gabrielle Soares Muniz; Passamani, Marcelo (Check list (Luís Felipe Toledo), 2016)
Information about the occurrence of medium-sized and large mammals in the Cerrado and the Atlantic Forest is essential for monitoring the conservation status of these species in such biodiversity hotspots. This study presents the results of a survey of medium-sized and large mammals from Quedas do Rio Bonito Ecological Park, located in an ecotone between Cerrado and Atlantic Forest in Southeastern Brazil. Four sampling methods were used: sand plots, camera traps, line transects and tomahawk traps. We recorded 20 species belonging to 12 families and 7 orders, with a high occurrence of Carnivora (50%). We highlight the occurrence of five endangered species: Chrysocyon brachyurus, Leopardus pardalis, L. guttulus, Puma yagouaroundi and P. concolor. The species with the highest frequencies of occurrence were P. concolor (27%), C. brachyurus (17%), and Sylvilagus brasiliensis (13%). Our results confirm that, despite their small size, forest fragments are essential for “top-of-the-chain” species conservation in the region.